Pengaruh Beban Kerja Dan Kompensasi Terhadap Kinerja Karyawan Pada PT Telkom Group Cabang Kota Palopo - Citra Ramadhani Ichlas; Yusi Yusi; Nurhikma Aulia; Budiarti Purti Uleng (Movere Journal, 2026)
This study aims to analyze and determine the influence of workload andcompensation on employee performance at PT Telkom Group Palopo City Branch. Thetype of research conducted is quantitative. The type of data used consists of primary andsecondary data. Data collection was carried out through observation and questionnaires.The number of samples used was 60 employees. The data analysis methods used aredescriptive analysis, validity testing, reliability testing, and multiple linear regressionanalysis. The results of the study indicate that, simultaneously, workload and compensationhave a significant influence on employee performance. Partially, the provision of workloadhas a significant positive effect on employee performance at PT Telkom Group Palopo CityBranch, whereas compensation does not have a significant effect on employeeperformance.